(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Hotel Management Institutes have seen a tremendous growth in the recent years. More and more students are inclining to pursue the course at the national level in various institutes. Selecting a career path is very significant step in person’s life as it helps to decide how they would live rest of their life. Many factors affect the career choices of an individual. Understanding applicant’s preferences and values become an important aspect for recruiters to develop and update recruitment strategies. Objective: The purpose of the study was to find out the factors influencing the choices of undergraduates during the campus recruitment at IHM, Pusa. Methods: The subjects comprised of students (n=50) from Institute of Hotel Management, Pusa, New Delhi. Questionnaire was used as a tool to gather data on the various factors influencing the career choices. Results: The findings showed that the factors such as job stability & security prospects provided by the company, brand reputation, level of entry in the company highly affects the choices of undergraduates while making a career choice or applying for the recruitment process. Personal factors such as financial condition of home, parental consent, and job location also affects the choices of students to a great extent. Conclusion: Hence it becomes very important for the recruiter to understand the needs of the students to decrease the attrition rate & reduce the recruitment costs.